Thermotolerant yeasts capable of producing bioethanol: isolation from natural fermented sources, identification and characterization - Ali Azam Talukder; Farhana Easmin; Siraje Arif Mahmud; Mamoru Yamada (Biotechnology & Biotechnological Equipment, 2016)
Recently, the demands of biofuels have increased, because of their significant role in reducing various pollutants created by fossil fuels. Here, we have collected 25 samples containing various thermotolerant microorganisms from the nine natural fermented sources of Bangladesh, such as Boiled potato (Bp), Decomposed foods (Df), Municipal liquid waste (Mlw), Municipal solid waste (Msw), Sugarcane juice (Sc), Pantavat (Pv), Sugar molasses (Sm), Tari (Tari) and Watermelon juice (Wm) for bioethanol production. Among them, 18 isolates are capable of producing bioethanol. Cultural, morphological, physiological, biochemical and genetic analyses were carried out under various physiological conditions. Ethanol fermentation was checked by different carbon sources, temperatures and pH. All of the isolates could grow well in the medium containing Dextrose and Arabinose and only two strains Pv-1 and Bp-2 could ferment Xylose as a sole carbon source. At 42 °C, the highest ethanol concentration 6.58% (v/v) was obtained by a strain Wm-1 isolated from Watermelon juice. At 37 °C, maximal ethanol concentrations of 6.74% (v/v), 6.50% (v/v) and 6.22% (v/v) were obtained by the strains Bp-2, Wm-l and Pv-1, respectively. Among the various pH tested, the highest ethanol concentration 6.6% (v/v) was obtained at pH 4.5 by a strain named Tari-2. Finally, yeast 26S rDNA sequencing information identified the strains Sc-2 as Saccharomyces cerevisiae Pv-2, Tari-2 and Df-1 as Pichia kudriavzevii, Mlw-l and Bp-2 as Candida tropicalis, Pv-1 as Pichia guilliermondii and Df-2 as Candida rugosa.